ASSESSMENT OF QUALITY OF LIFE OF CHRONIC KIDNEY DISEASE PATIENT ATTENDING IN SELECTED HOSPITALS, WEST BENGAL - Chakraborty, Sima; Kundu, Mousumi; Mukherjee, Chandrani (International Journal of Research -GRANTHAALAYAH, 2024)
Introduction: Chronic Kidney disease (CKD) is still a health problem in India & increasing number of new cases. profound physiological, psychological, social effect due to CKD hurt the quality of life. Aim: This study aims to find out quality of life of CKD patient and association between quality of life with demographic variables. Method: The investigator conducted a descriptive study on assessment of quality of life (QOL)among chronic kidney disease patients attending selected Nephrology and Medicine OPD of West Bengal with the objective to assess quality of life and to find out the association between quality of life and selected demographic variables. The conceptual framework adopted for the study was based on Sr. Callista Roy’s adaptation model (1989). Non-probability convenience sampling technique was adopted to select 173 respondents. The tools used for the study were semi-structured interview schedule and WHOQOL-BREF. Result: The study findings revealed that the majority of the respondents (69.37%) had an average quality of life. The result also showed that respondents had maximum quality of life in social domain and minimum quality of life in psychological domain. A significant association found between quality-of-life score and addiction as chi- square value was 4.782=3.841] at 0.05 level of significance. The study has several implications in Nursing education, practice, administration, and research. The study concluded with recommendations for future intervention and improve policy implementation regarding CKD clinics for improving the quality of life among this population.